Plant Growth Stimulators Improve Two Wheat Cultivars Salt-Tolerance: Insights into Their Physiological and Nutritional Responses - Neveen B. Talaat; Alaa M. A. Hanafy (Plants, 2022)
Spermine (SPM) and salicylic acid (SA), plant growth stimulators, are involved in various biological processes and responses to environmental cues in plants. However, the function of their combined treatment on wheat salt tolerance is unclear. In this study, wheat (Triticum aestivum L. cvs. Shandawel 1 and Sids 14) plants were grown under non-saline and saline (6.0 and 12.0 dS m–1) conditions and were foliar sprayed with 100 mgL−1 SA and/or 30 mgL−1 SPM. Exogenously applied SA and/or SPM relieved the adverse effects caused by salt stress and significantly improved wheat growth and production by inducing higher photosynthetic pigment (chlorophyll a, chlorophyll b, carotenoids) content, nutrient (N, P, K+, Ca2+, Mg2+, Fe, Zn, Cu) acquisition, ionic (K+/Na+, Ca2+/Na+, Mg2+/Na+) homeostatics, osmolyte (soluble sugars, free amino acids, proline, glycinebetaine) accumulation, protein content, along with significantly lower Na+ accumulation and chlorophyll a/b ratio. The best response was registered with SA and SPM combined treatment, especially in Shandawel 1. This study highlighted the recovery impact of SA and SPM combined treatment on salinity-damaged wheat plants. The newly discovered data demonstrate that this treatment significantly improved the photosynthetic pigment content, mineral homeostasis, and osmoprotector solutes buildup in salinity-damaged wheat plants. Therefore, it can be a better strategy for ameliorating salt toxicity in sustainable agricultural systems.